(untitled) - Christopher, Robert C. (London, 1983)
This is a superb book, with the insight and wisdom of nearly 40 years of thoughtful study and first-hand experience. It combines personal vignettes with a sympathetic, objective and up-to-the-minute grasp of virtually every aspect of Japanese society, as well as of the practical policy issues that now make the U.S.-Japan relationship at once vital and sensitive to possible change. The last chapter is particularly outstanding, but the whole deserves careful reading not only by Americans but perhaps particularly by Europeans. Into the bargain, the author writes with admirable clarity and simplicity of expression.
Keywords: Nhật Bản,Japan; Văn minh,Civilization